Niat Pembelian Kembali Pengguna Grabmart: Peran Pengalaman Pelanggan Pasca-Pembelian dan Citra Perusahaan - Aurea Beryl Nathania Bomer; Hetty Karunia Tunjungsari (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
Tujuan dari penelitian ini menguji pengalaman pelanggan online pasca pembelian yang memengaruhi kepuasan pelanggan dan niat pembelian kembali saat membeli makanan segar secara online pada e-commerce GrabMart. Ini juga mengeksplorasi peran citra perusahaan sebagai moderator. Sebuah survei online dilakukan di Jakarta dengan pemodelan persamaan struktural kuadrat terkecil parsial (PLS-SEM) digunakan untuk menganalisis data yang dikumpulkan dari 116 pembeli online makanan segar di Jakarta. Temuan yang didapat yaitu pengalaman pelanggan pasca pembelian secara signifikan mendorong niat pembelian ulang pelanggan dengan meningkatkan kepuasan pelanggan. Selain itu, untuk perusahaan dengan citra perusahaan yang baik, niat pembelian ulang pelanggan lebih mudah dipengaruhi oleh pengalaman pelanggan pascapembelian. Temuan ini menginformasikan perusahaan e-commerce GrabMart makanan segar tentang pengalaman pelanggan pascapembelian yang sebagian besar mendorong kepuasan pelanggan dan membantu mempertahankan pelanggan. Selanjutnya, ini menyiratkan bahwa perusahaan dengan citra perusahaan GrabMart yang baik harus menyediakan pengalaman pelanggan pasca pembelian berkualitas tinggi yang sesuai dengan citra karena konsekuensi yang terkait dengan pengalaman pelanggan pasca pembelian yang buruk bisa sangat parah. The purpose of this research is to examine the post-purchase online customer experience that influences customer satisfaction and repurchase intention when buying fresh food online at GrabMart e-commerce. It also explores the role of corporate image as a moderator. An online survey conducted in Jakarta with partial least squares structural equation modeling (PLS-SEM) was used to analyze data collected from 116 fresh food online shoppers in Jakarta. The findings obtained are that post-purchase customer experience significantly encourages customer repurchase intentions by increasing customer satisfaction. In addition, for companies with a good corporate image, customer repurchase intentions are more easily influenced by the customer's post-purchase experience. These findings inform fresh food e-commerce company GrabMart about the post-purchase customer experience that largely drives customer satisfaction and helps retain customers. Further, this implies that a company with a good GrabMart corporate image should provide a high-quality post-purchase customer experience befitting the image because the consequences associated with a poor post-purchase customer experience can be severe. The purpose of this research is to examine the post-purchase online customer experience that influences customer satisfaction and repurchase intention when buying fresh food online at GrabMart e-commerce. It also explores the role of corporate image as a moderator. An online survey conducted in Jakarta with partial least squares structural equation modeling (PLS-SEM) was used to analyze data collected from 116 fresh food online shoppers in Jakarta. The findings obtained are that post-purchase customer experience significantly encourages customer repurchase intentions by increasing customer satisfaction. In addition, for companies with a good corporate image, customer repurchase intentions are more easily influenced by the customer's post-purchase experience. These findings inform fresh food e-commerce company GrabMart about the post-purchase customer experience that largely drives customer satisfaction and helps retain customers. Further, this implies that a company with a good GrabMart corporate image should provide a high-quality post-purchase customer experience befitting the image because the consequences associated with a poor post-purchase customer experience can be severe.